Changes in body proportions of children and adolescents from Rzeszów during a 35-year period from 1978/79–2013/14 - Perenc, Lidia; Radochońska, Anna; Błajda, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Environmental conditions have been changing over the years and the body’s capacity to adapt affects human development, its growth and typogenesis. Aim. To confirm the secular trend in the population of children and adolescents aged 4 to 18 from Rzeszów in the last 35 years in terms of growing and differentiation body proportions. Materials and methods. In 2013/2014, a total of 1,563 children from Rzeszów were examined. The length of the trunk, the upper limb, the lower limb, the width of the shoulders and the width of the hips were measured and the following indices were calculated: trunk length, upper limb length, lower limb length, inter-limb, hip-shoulder and shoulder width. The data was subjected to statistical analysis and compared to the data collected in 1978/79, 1993/1994 and 2003/2004. Results. During the 35-year period, the following symptoms were observed: elongation of upper and lower limbs in both sexes, increase in shoulder width in boys from 15-18 years of age, and in girls generally in the entire examined age, tendency to decrease in hip width in both sexes in most age classes. Conclusions. The secular trend in the population of children and adolescents aged 4 to 18 from Rzeszów in the last 35 years regarding growth process and differentiating body proportions was confirmed.
Keywords: anthropometry; growth; proportion; secular trend